Montmorency Tart cherries (Prunus cerasus L.) modulate vascular function acutely, in the absence of improvement in cognitive performance. Issue 11 (19th December 2016) - Keane, K. M.; Haskell-Ramsay, C. F.; Veasey, R. C.; Howatson, G.
Abstract: Cerebral blood volume and metabolism of oxygen decline as part of human ageing, and this has been previously shown to be related to cognitive decline. There is some evidence to suggest that polyphenol-rich foods can play an important role in delaying the onset or halting the progression of age-related health disorders such as CVD and Alzheimer's disease and to improve cognitive function. In the present study, an acute, placebo-controlled, double-blinded, cross-over, randomised Latin-square design study with a washout period of at least 14 d was conducted on twenty-seven, middle-aged (defined as 45–60 years) volunteers. Participants received either a 60 ml dose of Montmorency tart cherry concentrate (MC), which contained 68·0 (sd 0·26) mg cyanidin-3-glucoside/l, 160·75 (sd 0·55) mean gallic acid equivalent/l and 0·59 (sd 0·02) mean Trolox equivalent/l, respectively, or a placebo. Cerebrovascular responses, cognitive performance and blood pressure were assessed at baseline and 1, 2, 3 and 5 h following consumption. There were significant differences in concentrations of total Hb and oxygenated Hb during the task period 1 h after MC consumption ( P ≤0·05). Furthermore, MC consumption significantly lowered systolic blood pressure ( P ≤0·05) over a period of 3 h, with peak reductions of 6±2 mmHg at 1 h after MC consumption relative to the placebo. Cognitive function and mood were not affected. These results show that a single dose of MC concentrate can modulate certain variables of vascular function; however, this does not translate to improvements in cognition or mood.